2012
DOI: 10.1021/la302916s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Surface-Attachment Functionality on the Aggregation, Persistence, and Electron-Transfer Reactivity of Chalcogenorhodamine Dyes on TiO2

Abstract: Figure S1. Normalized absorbance spectra of thiophene-substituted dyes (a) and phenyl-substituted dyes (b) in CH 3 OH.Figure S2. Absorbance spectra of 1-Se (a), 3-Se (b), 2-O (c), 4-O (d), 2-S (e), and 4-Se (f) dissolved in CH 3 OH and adsorbed to nanocrystalline TiO 2 films at various surface coverages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Electrostatic and noncovalent interactions of the dye with the polar surface and adjacent dye molecules may lead to the formation of an ordered assembly of dye aggregates on titania. Dye aggregation is known be the Achille’s heel of most of organic sensitizers, usually leading to intermolecular excited state quenching and, hence, reducing the DSCs photocurrent and overall power output. ,, The formation of stable aggregates on the TiO 2 surface is usually manifested by a considerable broadening and blue or red shift, depending on whether H- , or J-type of aggregates are formed, of the UV–vis absorption spectrum upon TiO 2 adsorption compared to that for of dyes in solution. , In some selected cases, a controlled aggregation has proven to enhance the photocurrent generation due to the larger light-absorption window of the aggregates, possibly combined to an efficient charge transfer from the aggregate excited state to the semiconductor. ,,, The use of antiaggregation coadsorbents, among which the most widely employed is chenodeoxycholic acid (CDCA), has been reported to effectively suppress dye aggregation on the TiO 2 surface, yielding to notably improved cell performances for dye being critically affected by aggregation. Because CDCA competes with the dye for TiO 2 absorption, thus, breaking undesired dye/dye intermolecular interactions, a general decrease of the dye loading is also typically observed with a consequent decrease of the light harvesting efficiency of the photoelectrode, which is however usually offset by an improved charge generation efficiency due to suppression of intermolecular excited state quenching and filtering effects.…”
Section: Introductionmentioning
confidence: 99%
“…Electrostatic and noncovalent interactions of the dye with the polar surface and adjacent dye molecules may lead to the formation of an ordered assembly of dye aggregates on titania. Dye aggregation is known be the Achille’s heel of most of organic sensitizers, usually leading to intermolecular excited state quenching and, hence, reducing the DSCs photocurrent and overall power output. ,, The formation of stable aggregates on the TiO 2 surface is usually manifested by a considerable broadening and blue or red shift, depending on whether H- , or J-type of aggregates are formed, of the UV–vis absorption spectrum upon TiO 2 adsorption compared to that for of dyes in solution. , In some selected cases, a controlled aggregation has proven to enhance the photocurrent generation due to the larger light-absorption window of the aggregates, possibly combined to an efficient charge transfer from the aggregate excited state to the semiconductor. ,,, The use of antiaggregation coadsorbents, among which the most widely employed is chenodeoxycholic acid (CDCA), has been reported to effectively suppress dye aggregation on the TiO 2 surface, yielding to notably improved cell performances for dye being critically affected by aggregation. Because CDCA competes with the dye for TiO 2 absorption, thus, breaking undesired dye/dye intermolecular interactions, a general decrease of the dye loading is also typically observed with a consequent decrease of the light harvesting efficiency of the photoelectrode, which is however usually offset by an improved charge generation efficiency due to suppression of intermolecular excited state quenching and filtering effects.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work demonstrated that most carboxylated cyanine dyes show evidence for aggregate formation in their incident photon-to-current conversion efficiency (IPCE) spectra. , Aggregated dye molecules have been observed in many DSSC systems and are usually assumed to be detrimental to DSSC performance as a result of excited-state quenching. Therefore, antiaggregation coadsobants are sometimes added to minimize dye–dye interactions. , Interestingly, there are several examples in which dye aggregation was shown to improve spectral coverage, quantum yields, and/or photocurrent; however, it is difficult to predict or control specific dye aggregates to enhance light-to-power conversion efficiencies. ,, Furthermore, the aggregation configuration of monocarboxylated dyes has been shown to change substantially over time, further complicating the use of dye aggregation to improve DSSC performance …”
Section: Introductionmentioning
confidence: 99%
“…Covalent bond formation between the dye molecule and the surface appears to be a better option than other modes of attachments mentioned above, as dyes attached via weaker modes of interaction tends to get removed while washing [5]. Dye molecules are immobilized on solid platforms through some specific functional group on the dye [5,[7][8][9][10][11] and typically carboxylic or phosphoric acid moieties on the dye have served this purpose well [12][13][14][15]. Linkers play an important role in tethering the dye molecules to the surface [16,17].…”
Section: Introductionmentioning
confidence: 99%